TRANSFORMASI DIGITAL DALAM MANAJEMEN SUMBER DAYA MANUSIA: TANTANGAN DAN PELUANG (STUDI KASUS PADA PERUSAHAAN MANUFAKTUR DI INDONESIA ) - Hanung Eka Atmaja; Jaka Permana; Zulfa Khairina Batubara; Winda Ardiani; Anggiat Parlindungan (ITB AAS Indonesia Surakarta, 2024)
This study aims to explore the challenges and opportunities faced by manufacturing companies in Indonesia in the process of digital transformation in the field of human resource management (HRM). Digital transformation is an important step for companies in improving operational efficiency and competitiveness in the Industry 4.0 era. The research method used is a case study with a qualitative approach, where data is obtained through in-depth interviews with HR managers, surveys to employees, and analysis of company documents. The results showed that the main challenges faced by the company were resistance to change, lack of digital skills among employees, and limited technological infrastructure. However, the research also identified a number of opportunities, such as improved work process efficiency, better employee data management, and increased employee engagement through digital platforms. Therefore, companies are advised to invest in digital skills training and technology infrastructure development to maximize the benefits of digital transformation.